Caminhos para o desenvolvimento estratégico na pesquisa e impulsionar o progresso na indústria farmacêutica brasileira - Schiavo, Verginia Therezinha Barros Maciel (2006)
In this investigation, we briefly evaluated the recent history of Brazilian Pharmaceutical Industry to examine the actual insight of its Research and Development, considering the innovation as its primary focus and the support of its Marketing networks primarily functioning as propeller for its growth. We critically evaluated published articles, periodicals, interviews, graphs including statistical data, and reports that were published in the past 6 years in numerous Brazilian publications concerning Brazilian and World Pharmaceutical Industry. We considered the actual tendencies of the pharmaceutical industry, i.e., a company’s internal administration, evaluating the response of the national pharmaceutical industry to the consolidation of multinationals companies resulting in large pharmaceutical conglomerates. In addition, we attempted to establish the influence of the national legislation including Pharmacosurveillance, not only considering their normative function, but also its fiscal control. The strong relation, if not association, between the markets and international institutions force the nations to develop their own strategies that comply with the potential interest as it relates to worldwide consumption. Brazil, recognized as the single biodiversity on the planet is the main key for the national pharmaceutical and chemical industry development. When one looks for an advantage in international competition, it is necessary to assess some priorities in the production chain such as the issue of Intellectual Property, among others, since without a legal system that assures the returns on extraordinary funds invested in new products development as well as to finance the machinery of the Research & Development Departments; we will have limited or no chance to be present and to grow worldwide with genuine Brazilian substances/products. Additionally, in order to transform our biodiversity in health and exchange value to our people, laboratories, and to the Brazilian investment (funds), besides the refinement of the legal system that involves the pharmaceuticals and chemicals production chain, we need to acquire methodologies to establish University-Industry partnerships through the diffusion of the: “Systematization of Research & Development applied to pharmaceutical companies and the consequent Implantation and management of their Quality Systems: the steps to be followed to integrate and grow in this market”